Historical Patterns of Mount Merapi Eruptions: Understanding the Century Cycle and Its Implications for Community Preparedness Education, 1768-2010 - Septian Aji Permana; Siti Zahrah Mahfood; Ary Purwatiningsih (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: Mount Merapi is one of the most active volcanoes in Indonesia, yet public understanding of its long-term eruption pattern remains limited. Most people are more familiar with short-term volcanic activity than with the possibility of major eruptions recurring within a longer historical cycle. This study aims to analyze the historical eruption pattern of Mount Merapi from 1768 to 2010 and to examine its implications for community preparedness education. The study uses the historical method, including heuristic data collection, source criticism, interpretation, and historiography. Primary and secondary historical sources on Merapi’s eruptions were critically reviewed and synthesized to identify long-term patterns and their social impacts. The findings show that Merapi’s major destructive eruptions tend to appear within a century-scale cycle, particularly the eruptions of 1930 and 2010, both of which caused severe casualties and widespread damage. The 2010 eruption was widely regarded as unexpected, but historical evidence suggests that it was part of a recurring long-term pattern. These findings reveal a gap between historical knowledge and public awareness of disasters. This study contributes to Indonesian disaster historiography by offering a long-term interpretation of volcanic disasters and by emphasizing the importance of integrating historical eruption records into disaster risk reduction and community preparedness education. Abstrak: Gunung Merapi merupakan salah satu gunung api paling aktif di Indonesia, tetapi pemahaman masyarakat tentang pola erupsi jangka panjangnya masih terbatas. Masyarakat umumnya lebih mengenal aktivitas vulkanik jangka pendek daripada kemungkinan terjadinya erupsi besar yang berulang dalam siklus sejarah yang lebih panjang. Penelitian ini bertujuan untuk menganalisis pola erupsi historis Gunung Merapi dari tahun 1768 hingga 2010 serta mengkaji implikasinya bagi pendidikan kesiapsiagaan masyarakat. Penelitian ini menggunakan metode historis yang meliputi heuristik, kritik sumber, interpretasi, dan historiografi. Sumber-sumber sejarah primer dan sekunder mengenai erupsi Merapi ditelaah secara kritis dan disintesis untuk mengidentifikasi pola jangka panjang serta dampak sosialnya. Hasil penelitian menunjukkan bahwa erupsi besar yang merusak di Merapi cenderung muncul dalam siklus skala abad, terutama pada erupsi tahun 1930 dan 2010 yang menimbulkan korban jiwa besar serta kerusakan luas. Erupsi 2010 selama ini dianggap tidak terduga, padahal bukti historis menunjukkan bahwa peristiwa tersebut merupakan bagian dari pola jangka panjang yang berulang. Temuan ini menunjukkan adanya kesenjangan antara pengetahuan sejarah dan kesadaran bencana masyarakat. Kajian ini berkontribusi pada historiografi bencana Indonesia dengan menawarkan pembacaan jangka panjang atas bencana vulkanik serta menegaskan pentingnya integrasi catatan erupsi historis ke dalam pengurangan risiko bencana dan pendidikan kesiapsiagaan masyarakat.